Sensory Characteristics and Hedonic Preferences of Sprinkle Chili Sauce with Variations in Kecombrang Proportion - Ulima Putri Nabilah; Mauren Gita Miranti; Hidayatun Musyasyaroh; Diwyacitta Antya Putri (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
Sprinkle  chili  sauce  represents  a  contemporary  chili  powder-derived  product  that  has  experienced  growing  consumer interest as a seasoning agent used to intensify the flavor profile of various dry food preparations. The present study was undertaken to examine the hedonic properties of dried kecombrang sprinkle chili sauce, establish the optimal product formulation,  and  characterize  the  selected  formula  across  varying  proportions  of  kecombrang  incorporation.  A quantitative descriptive experimental approach was adopted, encompassing six distinct treatment levels of kecombrang concentration,  specifically  50%,  60%,  70%,  80%,  90%,  and  100%.  Sensory  evaluation  was  carried  out  involving  35 semi-trained  panelists  with  a  culinary  arts  background,  who  assessed  each  product  formulation  against  five  sensory attributes:  color,  aroma,  texture,  taste,  and  overall  acceptability.  Statistical  analysis  was  performed  using  One  Way Analysis  of  Variance  (ANOVA),  subsequently  followed  by  the  Duncan  Multiple  Range  Test  (DMRT)  to  identify significant  differences  among  treatments  and  determine  the  most  preferred  formulation.  Findings  revealed  that variations  in  kecombrang  proportion  exerted  a  statistically  significant  influence  on  the  hedonic  quality  of  the  dried kecombrang  sprinkle  chili  sauce  across  all  evaluated  attributes.  Among  the  six  formulations  tested,  F1  (50% kecombrang)  emerged  as  the  most  favorable  treatment,  exhibiting  a  well-balanced  reddish-brown  appearance,  a characteristic  yet  subtle  kecombrang  aroma,  and  a  dry  texture  with  a  moderately  fine  consistency  that  aligned  most closely with panelist preferences.